Oil palm production, income gains, and off-farm employment among independent producers in Cameroon - Tabe-Ojong, Martin Paul Jr.; Molua, Ernest L.; Nanfouet, Marco Alberto; Mkong, Cynthia J.; Kiven, Vanessa; Ntegang, Venant Atem (Elsevier, 2023)
We examine the association of oil palm production with income and off-farm employment using a farm household survey of independent oil palm producers in Cameroon. Employing different regression techniques and empirical strategies, we find oil palm production to be associated with household income, a finding which is consistent with per capita income distribution. Exploring heterogeneity in the relationship between oil palm production and income, we show that oil palm production has the potential to benefit non-producers should they produce oil palm. Moving beyond effects at the mean and in the interest of understanding who benefits more from oil palm production, we also show that oil palm production is associated with income gains for all producers. This finding provides suggestive insights that oil palm production is inclusive and could stir development in rural areas. Assessing the implications on off-farm employment, we find empirical evidence that oil palm production reduces the likelihood of participation in off-farm employment. We, therefore, conclude that oil palm production could be a crucial and inclusive profitable venture to increase smallholder incomes and improve livelihoods in rural and forested environments, but significant potentials exist to make the sector more profitable, less labour-intensive and environmentally-friendly in native production zones.